2011
DOI: 10.1111/j.1360-0443.2011.03440.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trials in pregnancy: scientific and ethical aspects. Exposure to different opioid medications during pregnancy in an intra‐individual comparison

Abstract: Background Chronic medical conditions such as opioid dependence require evidence-based treatment recommendations. However, pregnant women are underrepresented in clinical trials. We describe the first within-subject comparison of maternal and neonatal outcomes for methadone vs. buprenorphine exposed pregnancies. Though methadone is the established treatment of pregnant opioid dependent women, recent investigations have shown a trend for a milder neonatal abstinence syndrome (NAS) under buprenorphine. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Several studies have recently been published that have demonstrated that buprenorphine offers a substantial efficacy advantage over the current standard of care with oral morphine (Kraft et al, 2011;Unger et al, 2011). Several studies have recently been published that have demonstrated that buprenorphine offers a substantial efficacy advantage over the current standard of care with oral morphine (Kraft et al, 2011;Unger et al, 2011).…”
Section: Pregnant Womenmentioning
confidence: 99%
“…Several studies have recently been published that have demonstrated that buprenorphine offers a substantial efficacy advantage over the current standard of care with oral morphine (Kraft et al, 2011;Unger et al, 2011). Several studies have recently been published that have demonstrated that buprenorphine offers a substantial efficacy advantage over the current standard of care with oral morphine (Kraft et al, 2011;Unger et al, 2011).…”
Section: Pregnant Womenmentioning
confidence: 99%
“…This indicates that fetal exposure does not necessarily result in NAS symptoms. Compared with methadone‐exposed neonates, buprenorphine‐exposed neonates usually experience a milder NAS course and a reduced need for pharmacotherapy . This clinical heterogeneity may result from the complex interplay of genetic, physiologic, and environmental factors.…”
mentioning
confidence: 99%
“…The Royal College of General Practitioners', using evidence from a comparison of two self-selected Scottish groups (Hepburn, 1997), suggest that methadone detoxification can be carried out 'at any speed and at any stage' during pregnancy (Ford et al, 2005). Others highlight nevertheless the poor maternal treatment outcomes observed following opioid detoxification, such as the high rate of relapse back to illicit drug use (Kashiwagi, Arlettaz, Lauper, Zimmermann, & Hebisch, 2005), which has been widely observed to be detrimental to neonatal outcomes (Hulse, Milne, English, & Holman, 1997;Unger et al, 2011). In this survey the likelihood of a CDTS recommending inpatient detoxification was doubled (0R = 2.28) when neonatologists, were involved in patient care.…”
Section: Discussionmentioning
confidence: 84%